Methods of specific laboratory testing of new coronavirus infection - O. A. Perevesentsev; T. O. Cholodnaya; A. E. Samsonov; D. V. Burtsev (Медицинский вестник Юга России, 2020)
The review presents a description of the specific laboratory testing of SARS-CoV-2. The effectiveness of certain types of tests depending on the set medical and epidemiological tasks is shown. The importance of using certain diagnostic methods for mass and rapid testing of patients for a new coronavirus infection, which will speed up their detection, was also noted. The effectiveness of using test systems that can be used in outpatient settings without the presence of a stationary laboratory in a medical facility is shown, which will simplify and increase the throughput of medical institutions that perform SARS-CoV-2 diagnostics. This review will be useful for both medical professionals of laboratory specialties and all clinical doctors who are currently working with a new coronavirus infection.